DETERMINANTS OF AGRICULTURAL LOAN ACCESS FROM FORMAL SOURCES IN CROSS RIVER STATE CENTRAL AGRICULTURAL ZONE, NIGERIA - O. I., Ettah; B. O., Ebu (International Journal of Research -GRANTHAALAYAH, 2018)
Formal agricultural loan is an important tool in agricultural development and key to agricultural modernization. This is because this source of loans enables farmers to have access to production inputs as well as adopt modern farm technologies. For agricultural development to be achieved and sustained, agricultural loan is required especially in the rural areas where majority of the populace are engaged in agriculture. The study set out to analyse the determinants of agricultural loan access from formal sources in Cross River State central agricultural zone, Nigeria and proffer policy recommendations based on the findings. A three-stage random sampling technique was employed to get a total of 100 respondents with the use of a detailed structured questionnaire. Descriptive statistics and multiple regression model were used to analyse the data. Result of the analysis showed that socio-economic characteristics of farmers such as: age, gender, occupational status, household size, educational level, farming experience, farm size, farm income, off- farm income, and labour use by respondents determined farmers access or otherwise to loan from formal sources and result of the logit regression model showed that age, education, farm size, collateral, farm income and cooperative membership all affected access of loan from formal sources positively, while farm experience do not determine access of loan from formal sources. The following recommendations were made: farmers in the area should be encouraged by government to enhance their educational level, more farmland should also be made available to increase their farm size and cooperative society’s membership should be encouraged by government.